THE TRANSLATION TECHNIQUES OF THE TRANSLATION DAMONO’S POEMS IN ENGLISH (ELite Journal : International Journal of Education, Language, and Literature, 2023)
Research on translation has recently been significantly developed in various types of texts. Although research on more specific types of poems has been conducted, this research is still researching the translation method, and it is still rare for such research to use translation techniques. Therefore, this study is interested in analyzing the techniques used by translators in translating a poem from the source language to the target language. Besides, this research aims to discover the techniques used in translating Sapardi Djoko Damono’s poems in the English translation. This research is a qualitative descriptive study in which the object of this research is Sapardi Djoko Damono’s poem in volume “Sihir Hujan” and its translation, “Black Magic Rain,” translated by Harry Aveling. 21 of 51 poems were chosen as the object of this research. The instrument used is a research instrument that is supported by observation sheets. In conducting this research, researchers need supporting instruments, namely the observation checklist. It was found that literal translation has become one of the most widely used translation techniques by Sapardi Djoko Damono’s poem translated by Harry Aveling. The results showed that there were 12 techniques out of 18 techniques were used in the 119 data poems. They are adaptation, amplification, borrowing, calque, compensation, discursive creation, generalization, linguistic amplification, linguistic compression, literal translation, modulation, and reduction.